Analytical validation of an automated assay to measure calprotectin (S100A8/A9) in dog saliva and serum and changes in canine leishmaniasis, pyometra and hyperadrenocorticism - Marina García-Camacho; Asta Tvarijonaviciute; Silvia Martínez-Subiela; José Joaquín Cerón; Alberto Muñoz-Prieto (BMC Veterinary Research)
Abstract Background Calprotectin (S100A8/A9) is a protein related to innate immunity that is considered a biomarker of inflammation. Currently, there is a commercially available automated assay for the measurement of calprotectin concentration (Bühlmann fCal Turbo® assay), which has been previously validated for saliva and serum of swine and for saliva of horses, and in the canine species it has been validated for use with fecal samples, but it has not been previously validated in canine saliva or serum. Thus, the aim of this study was to perform an analytical validation of an automated assay for the measurement of calprotectin in the saliva and serum of dogs. In addition, changes in this protein in saliva and serum of three diseases with different pathogenic mechanisms – leishmaniasis, pyometra and hyperadrenocorticism – were evaluated. Finally, in these diseases, the correlation of salivary and serum calprotectin with the serum levels of three acute phase proteins (APPs), including C-reactive protein (CRP), haptoglobin (Hp) and ferritin, was also assessed. Results The analytical validation results showed that the assay was precise (coefficients of variation < 15% in all cases), accurate (the dilutional parallelism for serum and salivary calprotectin showed observed-to-expected ratios with a mean of 96.9% and 97.2%, respectively), and presented a limit of detection of 0.038 mg/L. When this assay was applied to the different diseases, a significant increase in the concentration of salivary calprotectin in dogs with leishmaniasis (p = 0.0002) and in those with pyometra (p = 0.002), compared to healthy ones, was observed, whereas no significant differences were found in serum. Furthermore, a significant positive moderate correlation was obtained between salivary calprotectin and serum CRP (r = 0.5; p = 0.001) and haptoglobin (r = 0.5; p = 0.002), and between calprotectin and CRP (r = 0.67; p < 0.001) in serum. Conclusions Calprotectin (S100A8/A9) can be measured in dog saliva and serum samples by the automated method validated in this study, and when measured in saliva it could be used as a potential biomarker of inflammation and immune activation in the dog.